Turning numbers into knowledge : mastering the art of problem solving - Koomey, Jon (Analytics Press, 2008)
"Mastering the art of problem solving takes more than proficiency with basic calculations; it requires understanding how people use information, recognizing the importance of ideology, learning the art of storytelling, and acknowledging the important distinction between facts and values. Intended for professors, managers, entrepreneurs, and students, this guide addresses these and other essential skills. With clear prose, quotations, and exercises for solving problems in the real world, this book serves as an ideal training manual for those who are new to or intimidated by quantitative analysis and an excellent refresher for those who have more experience but want to improve the quality of their data, the clarity of their graphics, and the cogency of their arguments."--Publisher's description